If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -8y + 12 = 0 Reorder the terms: 12 + X + -8y = 0 Solving 12 + X + -8y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + X + -12 + -8y = 0 + -12 Reorder the terms: 12 + -12 + X + -8y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + X + -8y = 0 + -12 X + -8y = 0 + -12 Combine like terms: 0 + -12 = -12 X + -8y = -12 Add '8y' to each side of the equation. X + -8y + 8y = -12 + 8y Combine like terms: -8y + 8y = 0 X + 0 = -12 + 8y X = -12 + 8y Simplifying X = -12 + 8y
| D+(-22)=(-44) | | 2x-6(x-12)=28 | | 12a/3=8 | | 4c+12=7c+9.21 | | 5/13=c-3/8 | | 80=5/9(F-32) | | 3x+1=ln(13) | | -28x^2-186x-96=0 | | ln(x)=7.2 | | 3t/4=18 | | 10-2h=7a | | -4(-8+7x)=-52 | | 45-x/4+45-x/4+115=180 | | 5m+21=180 | | x+(3x-5)-(4x-7)=2 | | 4a+5a=450 | | 3a/4=36/15 | | x-2000/2000 | | 3(x-5)+2(6-x)=10 | | (7u-7x+2)(5u+3x)=0 | | 5(2r+4)=3(2r-9)+4r-7 | | 2x-5(x+6)=4(x-11) | | 2.8x+1.1y-5.3=0 | | 2msquared=26 | | -44=4(-4-7n)+7(-1+7n) | | 3(4x-5)=6(2x-5) | | 23+p=27 | | V=0.50r(2)h | | 7(3x+3)=21x+21 | | p^2-1/9 | | 58=5m+52 | | 14z-2/7=5/7 |